Search for squarks and gluinos in events with jets and missing transverse energy in p(p)over-bar collisions at root s-=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Agelou, M.; Agram, J. L.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; et al. (Elsevier, 2006)
The results of a search for squarks and gluinos using data from p over(p, ̄) collisions recorded at a center-of-mass energy of 1.96 TeV by the DØ detector at the Fermilab Tevatron Collider are reported. The topologies analyzed consist of acoplanar-jet and multijet events with large missing transverse energy. No evidence for the production of squarks or gluinos was found in a data sample of 310 pb-1. Lower limits of 325 and 241 GeV were derived at the 95% C.L. on the squark and gluino masses, respectively, within the framework of minimal supergravity with tan β = 3, A0 = 0, and μ < 0. © 2006 Elsevier B.V. All rights reserved.